2018
DOI: 10.1097/igc.0000000000001289
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hyperthermic Intraperitoneal Chemotherapy and Cytoreductive Surgery in the Treatment of Recurrent Uterine Sarcoma

Abstract: Our study is the first to compare survival outcomes of HIPEC versus conventional therapies for recurrent US and is suggestive of treatment benefit. Further studies with more patients and longer follow-up to evaluate the role of HIPEC in management of this disease are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…At relapse, she received surgery with cisplatin and doxorubicin HIPEC and receiving gemcitabine and docetaxel, all in a salvage attempt. Surgery with HIPEC has shown potential benefit in uterine sarcomatosis in recent small studies, though further validation in this area is warranted (Diaz-Montes et al, 2018). NCCN guidelines recognize ifosfamide and doxorubicin, gemcitabine and docetaxel, and several other combinations as viable treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…At relapse, she received surgery with cisplatin and doxorubicin HIPEC and receiving gemcitabine and docetaxel, all in a salvage attempt. Surgery with HIPEC has shown potential benefit in uterine sarcomatosis in recent small studies, though further validation in this area is warranted (Diaz-Montes et al, 2018). NCCN guidelines recognize ifosfamide and doxorubicin, gemcitabine and docetaxel, and several other combinations as viable treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 309 articles were identified from 3 electronic database searches, including 4 additional records from the review of reference lists and correspondence with field experts (Figure 1). After the removal of duplicates, initial title and abstract screening, followed by further evaluation of full texts, 20 articles published between 2004 and 2019 were eligible for final inclusion in the qualitative synthesis (Table 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. 18 articles further provided sufficient statistical information for meta-analysis, although Goéré et al ( 2017) was excluded due to potential overlap in subjects with other studies and Bryan et al (2014) was excluded as the primary histology was that of gastrointestinal stromal tumors (GIST), leaving 16 articles for quantitative synthesis [16-18, 20, 23, 24, 26-35].…”
Section: Study Selection and Participant Characteristicsmentioning
confidence: 99%
“…In addition to the histopathologic and radiologic diagnosis of PS, many studies specified additional eligibility criteria for CRS-HIPEC, including age, performance status, possibility of complete cytoreduction based on pre-operative imaging, absence of significant comorbidities and extra-abdominal/hepatic metastases, as well as satisfactory hepatic, renal, and bone marrow function. The extent of PS was quantified intra-operatively using the PCI in 13 studies [16, 17,21,23,25,27,[29][30][31][32][33][34][35], the Dutch simplified peritoneal cancer index (SPCI) in 1 study [18], by noting tumor size and number of nodules resected in 1 study [26], and not specified in 5 studies [19,20,22,24,28]. The degree of resection was quantified using the CC score in 16 studies [16-18, 20, 21, 23, 24, 26, 27, 29-35], and the residual tumor (R) classification in 4 studies [19,22,25,28].…”
Section: Study Selection and Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the role of hyperthermic intraperitoneal chemotherapy (HIPEC) associated with cytoreductive surgery has been investigated by few studies with good outcomes, whilst evidence on the role of neoadjuvant chemotherapy in this setting are very scanty. A recent retrospective study comparing overall survival of 25 patients with recurrent uterine sarcoma showed survival benefit of the group receiving surgery with subsequent HIPEC compared to surgery followed by chemotherapy or radiotherapy, surgery only or medical treatment alone [46].…”
Section: Role Of Surgery In Gynaecological Sarcomasmentioning
confidence: 99%